Experiences of dysmenorrhea and its treatment among allistic and autistic menstruators: a thematic analysis - Lauren J. Gray; Hannah Durand (BMC, 2023)
Abstract Background Dysmenorrhea (i.e., period pain) is common and debilitating. Autistic people are known to experience pain differently, yet little is known about the menstrual pain experiences of autistic menstruators relative to non-autistic peers. This study aimed to explore the experience of period pain and treatment uptake for period pain among allistic and autistic populations. Methods This study used a qualitative design and opportunity sampling approach. Thirty-seven participants (of whom 17 were autistic) were interviewed via video-conferencing software using a semi-structured topic guide. Transcriptions of interviews were analysed using Braun and Clarke's Reflexive Thematic Analysis. Data were initially analysed together for common themes. Autistic menstruators' data was subsequently analysed separately to elucidate the unique experiences of this group. Results A total of six themes were constructed from the data. Initial analysis determined three themes related to experiences of period pain and treatment uptake in both allistic and autistic menstruators. Social perception of menstruation was discussed, highlighting the normalisation of pain, the taboo nature, and gendered experience of menstruation, contributing to untreated menstrual pain. Issues within menstrual healthcare were also shared, including experiences of ineffective treatment, dismissive interactions, and insufficient menstrual education. Impaired functionality was repeatedly highlighted, with menstruators detailing significant limitations to their usual functioning due to menstrual pain and ineffective treatment. Three further themes were constructed from separate analysis of data from autistic menstruators. Autistic menstruators discussed the impact of menstruation on their sensory experiences and needs, with many identifying overstimulation during menstruation. Social exclusion was discussed as a factor contributing to the experience of menstrual pain and poor treatment uptake. The final theme identified pain communication differences between autistic and allistic menstruators resulting in reports of ineffective treatment and challenges in healthcare interactions. Conclusions Communication differences, sensory aspects, and social factors contributed to the experience of period pain and treatment uptake for autistic menstruators. The perception of menstruation within society was highlighted by allistic and autistic menstruators as influential to their pain experience and engagement with treatment. Functionality was significantly impacted by pain for this sample. The study highlights societal and healthcare factors that could be improved to ensure accessibility of support and treatment for menstrual issues.